Native American DNA: Tribal Belonging and the False Promise of Genetic Science - TallBear, Kim (University of Minnesota Press, 2013)
Who is a Native American? And who gets to decide? From genealogists searching online for their ancestors to fortune hunters hoping for a slice of casino profits from wealthy tribes, the answers to these seemingly straightforward questions have profound ramifications. The rise of DNA testing has further complicated the issues and raised the stakes. In Native American DNA, Kim TallBear shows how DNA testing is a powerful-and problematic-scientific process that is useful in determining close biological relatives. But tribal membership is a legal category that has developed in dependence on certain social understandings and historical contexts, a set of concepts that entangles genetic information in a web of family relations, reservation histories, tribal rules, and government regulations. At a larger level, TallBear asserts, the "markers" that are identified and applied to specific groups such as Native American tribes bear the imprints of the cultural, racial, ethnic, national, and even tribal misinterpretations of the humans who study them. TallBear notes that ideas about racial science, which informed white definitions of tribes in the nineteenth century, are unfortunately being revived in twenty-first-century laboratories. Because today's science seems so compelling, increasing numbers of Native Americans have begun to believe their own metaphors: "in our blood" is giving way to "in our DNA." This rhetorical drift, she argues, has significant consequences, and ultimately she shows how Native American claims to land, resources, and sovereignty that have taken generations to ratify may be seriously-and permanently-undermined.